Survival differences among patients with hepatocellular carcinoma based on the stage of disease and therapy received: pre and post sorafenib era - Shah, Chintan; Mramba, Lazarus K.; Bishnoi, Rohit; Bejjanki, Harini; Chhatrala, Hardik Satish; Chandana, Sreenivasa R. (Journal of Gastrointestinal Oncology; Vol 8, No 5 (October 19, 2017): Journal of Gastrointestinal Oncology, 2017)
Background: The incidence of hepatocellular carcinoma (HCC) is increasing. Development of newer therapeutic modalities has changed the paradigm of HCC treatment in recent years. So, the aim of our study is to analyze the impact of these treatment modalities into the survival of HCC patients, based on the stage of HCC in real life practice. Methods: We analyzed the data from the SEER database: Incidence − SEER 18 Regs Research Data + Hurricane Katrina Impacted Louisiana Cases, Nov 2015 Sub (1973–2013 varying). Relative survival rates (RSRs) and hazard ratios (HRs) were measured for patients diagnosed with HCC between 2001 and 2013. Rates were compared between pre sorafenib [2001–2007] and post sorafenib [2008–2013] eras. Results: A total of 50,088 patients (21,435 in pre sorafenib era and 28,653 in the post-sorafenib era) were included with HCC from SEER database. The median relative survival for the entire population was 14 months with 5-year RSR of 21.20%; 11 months for those diagnosed in 2001–2007 with 5-year RSR 19.30% and 17 months for those diagnosed in 2008–2013 with 5-year RSR 22.40% (P